Provider perspectives on general practice in Henan, China: a mixed-methods study. Issue 2 (3rd February 2020) - Zhu, Jiming; Ariana, Proochista
Abstract : Objective: Since 2011 China's central government has committed to establishing a new 'general practitioner' (GP)-centred primary care system. To this end there have been great efforts to train an additional 300 000 GPs by 2020. This paper examines the perspective of practitioners in Henan, China, regarding general practice. Design: A mixed-methods approach using focus group discussions (FGD), and structured questionnaires. Setting/participants: Seven FGDs and responses to 1887 questionnaires included medical students, primary care doctors and GP residents in Henan. Results: The three surveyed medical groups have some awareness of the attributes of general practice (eg, comprehensiveness, first contact and coordination), but often misinterpret what being a GP entails. Five themes were identified through the FGDs and tested quantitatively for their prevalence with structured questionnaires. First, the GPs' role as a comprehensive care provider was (mis)interpreted as an 'all-round doctor'. Second, the GP's responsibility as the first point of care was understood in two conflicting ways: private personal doctors of the rich and the powerful or village doctors for common people. Third, referral was understood as simply guiding patients to appropriate departments within the hospital while the gatekeeping role was interpreted to involve GPs being peoples' health protectors rather than being also gatekeepers of specialty services. Traditional Chinese medicine now further complicates the understanding of GPs. And lastly, the GPs' main responsibility was considered to be public health work. Conclusion: The misunderstandings of the roles and responsibilities of GPs render problematic the policy foundation of China's GP-centred primary care system. Pursuing the quantity of GPs on its own is meaningless, since the number needed depends on the delineated role of GPs. Top priority is to establish clarity about the GP role, which requires reforming the health delivery system to address issues with fragmented care, strategically taking into account the development of GPs with work delegation and substitution and providing more clarity on the distinction between general practice and public health.